Thermal effects on metabolic rate in diapausing Pieris rapae butterflies - Emily E. Mikucki; Cole Julick; Justin L. Buchanan; Kristi L. Montooth; Brent L. Lockwood (Current Research in Insect Science)
ABSTRACT: As ectotherms, many insects spend the winter months in a state of suspended animation (i.e., diapause), lowering their metabolic rates to subsist on a limited store of energy reserves. The ability to lower metabolic rate during diapause relies, in part, on cold winter temperatures to intrinsically lower metabolic rate. Winter warming associated with global climate change may pose a challenge to diapausing insects by intrinsically increasing metabolic rate, potentially leading to the exhaustion of energetic reserves. We used stop-flow respirometry to measure oxygen consumption in response to temperatures representative of both acute and chronic winter warming scenarios in diapausing Pieris rapae pupae. Metabolic rate increased with increasing temperature in diapausing pupae, but metabolic rate depended on both pupal age and warming severity, with older pupae having lower metabolic rates overall. Despite the increases in metabolic rate, pupae recovered metabolic rate within 24-hours after short-term acute-warming exposure. In contrast, chronic exposure to warming over weeks and months led to significant decreases in metabolic rate later in diapause, as well as reductions in pupal mass. These results demonstrate that while respiration was thermally responsive, warming did not lead to sustained increases in metabolic rate. Instead, diapausing P. rapae appear to acclimate to higher temperature by lowering their metabolic rates in response to months of chronic warming. Overall, these patterns suggest that this species could be resilient to winter warming, at least in the context of energetics. However, the precise mechanisms underlying these responses remain to be characterized. Thus, future research—e.g., on the genetic underpinnings of energetics in the context of warming—could further elucidate the relative vulnerability of diapausing insects to future winter warming.